A dimensão sociocultural da reforma psiquiátrica: articulando redes para a consolidação da estratégia de atenção psicossocial - Liberato, Mariana Tavares Cavalcanti (2011)
This thesis aims to discuss on articulations that have been produced on the socio-cultural field in the Psychiatric Reform process and its pertinence to the streghtening of Psychosocial Care Strategy (EAPS) in Fortaleza/CE. Such interest has been justified by the need to promote not only the production of these networks, but also interfaces to enable strategies of support and sociability from the perspective of deinstitutionalization of madness. We were inspired by the cartography perspective of Deleuze e Guattari, and determined as objectives: 1) to discuss the complexity of Psychiatric Reform process and analyze the EAPS as a model for the current Mental Health policy in the country; 2) to map socio-cultural strategies connected to the CAPS network in the city, investigating experiences that already exist or may be constituted as everyday social support networks; 3) from that mapping to start, define and discuss some aspects that converge to the accomplishment for this new mental health paradigm, drawing a cartography of the issues and movements in progress. The mapping was carried out in 2009 and consisted of semi-structured interviews with the coordinators of the 14 existent CAPS and with some people connected to the Coordination of Mental Health. Besides, during the whole development of the study, we have taken part in public events that brought us clues on the connection between mental health and culture. From the survey produced, we defined three vectors for discussion (Art, Labour and Partnership with Social Movements) which have been highlighted as effective possibilities of intervention in the socio-cultural field of Psychiatric Reform in Fortaleza and reveal important paths on the fulfillment process of a new pattern of care. For each of these axes, we chose a field of empirical research (Projeto Arte e Saúde, COOPCAPS e MSMCBJ) in which we could better understand their strengths and difficulties, starting from open interviews with some of their actors and the production of a diary of sensations in 2010. We have seen that they are articulated with the proposal of EAPS, being part of the concerns to the National Mental Health Policy and also the municipal administration. However, we have noticed to be necessary to promote those dimensions further, focusing on its complexity at the macro and micro policies, with the purpose of leading the Psychiatric Reform process